2011
DOI: 10.1074/jbc.m111.239053
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A Protein Interacts with Human Immunodeficiency Virus Type 1 Gag Protein and Contributes to Productive Particle Assembly

Abstract: HIV-1 Gag precursor directs virus particle assembly and release. In a search for Gag-interacting proteins that are involved in late stages of the HIV-1 replication cycle, we performed yeast two-hybrid screening against a human cDNA library and identified the non-muscle actin filament cross-linking protein filamin A as a novel Gag binding partner. The 280-kDa filamin A regulates cortical actin network dynamics and participates in the anchoring of membrane proteins to the actin cytoskeleton. Recent studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 73 publications
1
46
0
3
Order By: Relevance
“…By far, the most specifically biotinylated cellular protein was the cytoskeleton-associated protein, Filamin A. Previous research has shown that the PrGag CA domain is necessary for efficient binding to Filamin A and supports a model in which binding of PrGag to Filamin A induces a reorganization of the cortical actin network to permit PrGag delivery to the PM via actin filaments (77). Our MS results support this model, although we did observe a difference between the MABirA* and ⌬MA-BirA* samples in the levels of Filamin A biotinylation; this may simply denote a relative preference of the ⌬MA-BirA* PrGag protein for self-biotinylation versus biotinylation in trans or it may indicate that, although MA does not bind to Filamin A, it is partially responsible for trafficking PrGag proteins to Filamin A binding sites.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…By far, the most specifically biotinylated cellular protein was the cytoskeleton-associated protein, Filamin A. Previous research has shown that the PrGag CA domain is necessary for efficient binding to Filamin A and supports a model in which binding of PrGag to Filamin A induces a reorganization of the cortical actin network to permit PrGag delivery to the PM via actin filaments (77). Our MS results support this model, although we did observe a difference between the MABirA* and ⌬MA-BirA* samples in the levels of Filamin A biotinylation; this may simply denote a relative preference of the ⌬MA-BirA* PrGag protein for self-biotinylation versus biotinylation in trans or it may indicate that, although MA does not bind to Filamin A, it is partially responsible for trafficking PrGag proteins to Filamin A binding sites.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, over half of the biotinylated proteins have been (Table 2, far right column) (22,26,35,36,42,50,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)85). As can be seen, the list includes a variety of translation factors, cytoskeleton-associated proteins, membrane proteins, and RNA-processing proteins: these are discussed in more detail below.…”
Section: Biotinylated Proteins In Virus Particlesmentioning
confidence: 99%
“…Nonetheless, the actin cytoskeleton might play an important role in virus assembly and production, since its drug-mediated inhibition changes the intracellular localization of Gag and diminishes virus production in T cells (36)(37)(38). In addition, small interfering RNA (siRNA) depletion of Filamin A, a host cell protein that regulates actin network dynamics, impairs viral particle assembly and release (39). Other cell effectors that regulate actin turnover, such as LIMK1 and ROCK1, were recently described to play a role in retrovirus release (40).…”
mentioning
confidence: 99%
“…In addition to viral determinants required for productive particle assembly and release, some cellular factors have been identified to be involved in these events (11,14,30,37,38,71,75). One example of these host factors is the AP-3 complex (22).…”
mentioning
confidence: 99%